State High School Religious Education Teachers ‘Strategies in Minimizing the Occupation of Interreligious Marriages in the Regency of North Minahasa - Nasruddin Yusuf; Mustafa Mustafa (STAI Hubbulwathan Duri, 2023)
Marriage is said to be valid in the Unitary State of the Republic of Indonesia if it is performed according to their respective religions as regulated in Law Number 16 of 2019 amendment to Law Number 1 of 1974 Concerning Marriage, in Article 2 paragraph (1) which reads